Hungarian Monitoring, 20 September 1988 . [Magyar rádiófigyelő], 1988. szeptember 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Polish government remains in office as caretaker - Renewed disturbances in Karabakh hill region - West German Christian parties mobilize against Romanian village destructions Domestic Affairs: - Mátyás Szűrös travels to Romania - Government's position on the Gabčíkovo-Nagymaros dam construction - Ferenc Kárpáti travels to the USSR - Political Committee in session - Interior minister István Horváth speaks on the rule of law at a criminology conference - Püski Press opens Economy: - Viability of National Association of Entrepreneurs (VOSZ) Külpolitika - Ügyvezetőként még hivatalban marad a lengyel kormány - Felújultak a zavargások a Karabah-hegyvidéken - A nyugatnémet keresztény pártok a romániai falurombolás ellen mozgósítanak Belpolitika: - Szűrös Mátyás Romániába utazott - A kormány álláspontja a bős - Nagymarosi építkezés ügyében - Kárpáti Ferenc a Szovjetunióba utazott - A PB ülése - Horváth István belügyminiszter a jogállamiságról egy kriminalisztikai konferencián - Megnyílt a Püski Nyomda Gazdaság: - A VOSZ életképessége